2015
DOI: 10.1016/j.ajpath.2015.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid Limits Pancreatic Recovery after Pancreatitis by Inhibiting Histone Deacetylases and Preventing Acinar Redifferentiation Programs

Abstract: The mechanisms by which drugs induce pancreatitis are unknown. A definite cause of pancreatitis is due to the antiepileptic drug valproic acid (VPA). On the basis of three crucial observationsdthat VPA inhibits histone deacetylases (HDACs), HDACs mediate pancreas development, and aspects of pancreas development are recapitulated during recovery of the pancreas after injurydwe hypothesized that VPA does not cause injury on its own, but it predisposes patients to pancreatitis by inhibiting HDACs and provoking an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…In support of this hypothesis, two recent studies showed that in vivo treatment with the pan-HDAC inhibitors sodium butyrate and trichostatin A (TSA), which target both class I and class II HDAC subfamilies, alleviated pancreatic damage, inflammation and fibrosis following L-arginine- (Kanika et al, 2015) or taurocholic acid-induced pancreatitis (Hartman et al, 2015) in rodents. However, in another study treatment with valproic acid had a detrimental effect on cerulein-induced pancreatitis, consequently delaying tissue recovery and reducing acinar cell proliferation (Eisses et al, 2015). These conflicting results highlight the need to further investigate the precise role of HDAC isoforms in this disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of this hypothesis, two recent studies showed that in vivo treatment with the pan-HDAC inhibitors sodium butyrate and trichostatin A (TSA), which target both class I and class II HDAC subfamilies, alleviated pancreatic damage, inflammation and fibrosis following L-arginine- (Kanika et al, 2015) or taurocholic acid-induced pancreatitis (Hartman et al, 2015) in rodents. However, in another study treatment with valproic acid had a detrimental effect on cerulein-induced pancreatitis, consequently delaying tissue recovery and reducing acinar cell proliferation (Eisses et al, 2015). These conflicting results highlight the need to further investigate the precise role of HDAC isoforms in this disease.…”
Section: Introductionmentioning
confidence: 99%
“…However, care has to be applied in the choice of HDAC inhibitor used, as treatment with valproic acid, an anti-epileptic drug that also has anti-HDAC activity, has been associated with the development of pancreatitis in humans (Gerstner et al, 2007) and with disease exacerbation in mice, manifested by increased inflammation, decreased proliferation and persistent acinar dedifferentiation with non-resolving ADMs (Eisses et al, 2015).…”
Section: Ms-275 and Adm Formationmentioning
confidence: 99%
“…The method reported in Refs. 19 and 20 is also a supervised learning segmentation framework for pancreatic histopathological images, but is based on pixel-wise classification. Thus, the method in (10, 11) is included for comparison.…”
Section: Resultsmentioning
confidence: 99%
“…Wnt/β-catenin signaling is one of the embryonic pathways, which is reactivated in ADMs following caerulein-induced pancreatitis (53,54). However, for the ADMs to re-differentiate into acinar cells wnt-signaling has to be eventually downregulated, as persistent wnt/β-catenin activity leads to impaired acinar recovery (24,53). The precise mechanism for the dynamic activity of wnt/β-catenin in ADMs is not clear, but a recent report implicates HDACs as an important epigenetic switch required for controlling nuclear β-catenin transcriptional activity (24).…”
Section: Caerulein-induced Pancreatitismentioning
confidence: 99%
“…However, for the ADMs to re-differentiate into acinar cells wnt-signaling has to be eventually downregulated, as persistent wnt/β-catenin activity leads to impaired acinar recovery (24,53). The precise mechanism for the dynamic activity of wnt/β-catenin in ADMs is not clear, but a recent report implicates HDACs as an important epigenetic switch required for controlling nuclear β-catenin transcriptional activity (24). The transcriptional factor PDX1 has primarily been associated with the embryonic pancreas and mature β-cells in the adult pancreas.…”
Section: Caerulein-induced Pancreatitismentioning
confidence: 99%